Challenges of Law Enforcement in Combating Cryptocurrency Based Money Laundering In Indonesia - Widiartana, Gregorius (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The rapid development of cryptocurrency as a digital financial asset has introduced new challenges for the prevention and eradication of money laundering crimes. While cryptocurrencies offer efficiency, decentralization, and borderless transactions, these very characteristics also create significant vulnerabilities for misuse, particularly in facilitating illicit financial flows. In Indonesia, the existing legal framework on anti-money laundering, primarily regulated under Law Number 8 of 2010, was formulated prior to the widespread adoption of cryptocurrency and therefore faces limitations in addressing technology-driven financial crimes. This article examines the challenges of law enforcement in combating cryptocurrency-based money laundering in Indonesia through a normative juridical approach. The study analyzes relevant statutory regulations, institutional authority, and enforcement mechanisms involving agencies such as PPATK, Bappebti, the Financial Services Authority, and law enforcement bodies. The findings indicate that law enforcement faces substantial obstacles, including regulatory fragmentation, jurisdictional complexities, difficulties in tracing blockchain-based transactions, evidentiary constraints, and limited technical capacity among enforcement institutions. Furthermore, the absence of comprehensive regulation concerning decentralized finance and non-custodial digital wallets exacerbates enforcement difficulties. This article argues that without regulatory harmonization, enhanced institutional coordination, and the integration of technological capabilities into law enforcement practices, the Indonesian legal system risks lagging behind the evolving landscape of financial crime. Strengthening adaptive legal frameworks is therefore essential to ensure effective anti-money laundering enforcement in the digital asset era.